Методичні підходи до удосконалення економічної оцінки природного багатства України - Бистряков, І.К.; Клиновий, Д.В. (Економіка природокористування і охорони довкілля, 2014)
Статтю присвячено питанням удосконалення методологічних засад економічної оцінки природного багатства України. Метою дослідження є визначення напрямів подальшого розвитку методів адекватної покомпонентної та комплексної оцінки природного капіталу в системі національного багатства країни з урахуванням питань їх адаптації до впровадження в господарську практику. Зосереджено увагу на проблемних аспектах існуючих методик оцінки природних ресурсів як таких, що недостатньо відображають актуальну цінність та економічну вартість природного багатства. Наголошено на необхідності розгляду цінності природного багатства з позицій вартісного визначення природного капіталу, зважаючи на його системні властивості. Визначено, що головною проблемою на шляху вдосконалення методів оцінки природного багатства є урахування актуальної, проте прихованої та неви- явленої наявними сучасними методиками вартості природного багатства, яка становить помітну частку сукупного природного капіталу. Поряд із господарськими характеристиками природних ресурсів, пов’язаних з їх фізичною наявністю, запропоновано враховувати також їх визначення в якості капітального активу, що супроводжується відповідними дисконтними ставками як показниками, що визначають норму прибутку та ступінь віддачі від використання природного капіталу в галузях економіки.
Підкреслено необхідність переосмислення значущості фактору природної ренти, ризику використання природоресурсного капіталу, врахування специфічних відтворювальних та екосистемних властивостей природного капіталу тощо.
Визначено, що для забезпечення повномірної оцінки природного багатства поряд із застосуванням наявних методик нормативних розрахунків з використанням даних державних оціночних реєстрів природних ресурсів необхідно також застосовувати розрахункові методи, що побудовані на базі нововведених показників економічної оцінки природного капіталу. Наголошено, що економічна оцінка природного багатства на засадах суттєвого вдосконалення системи показників обліку має сформувати можливості кардинального покращення системи управління процесом раціонального використання й охорони природних ресурсів. The article is dedicated to issues as to improvement of methodological bases of the economic assessment of natural wealth of Ukraine. The aim of the article is to determine the directions of the further development of the methods of appropriate componentwise and compre- hensive assessment of the natural capital in the system of country’s national wealth, taking into account the questions of their adaptation to implementation in economical practice. The attention is concentrated on problem aspects of the existing methods of the assessment of the cost of natural resources, as such insufficiently representing actual value and economic cost of the natural wealth.
The stress is laid on the need to consider the value of the natural wealth based on the determination of the cost of natural capital taking into account its system characteristics. It is determined that the main problem on the way of the improvement of methods of the natural wealth assessment is accounting of actual, but hidden and not shown by available modern methods, value of natural wealth being a considerable part of the joint natural capital It is offered to take into account, equally with the economical features of natural resource, connected with their physical presence, also their cost as a capital active, which is accompanied by the corresponding discount rates as a factor defining the rate of the profit and the degree of the feedback from the use of the natural capital in the economic sectors. The solving of the problem of the assessment of natural wealth may be performed in three main conditions: the first – to confess the revenue approach to be principal in assessment of the natural capital, on the same level with the other approaches; the second – obligatory accounting of ecological and social value of natural resources; the third – the expansion of the list of valued resources and accounting of the natural system ecological capital. It is emphasized on the need to reconsider the role of natural rent factor’s importance, the risk of using the natural capital. It is determined that in order to secure full-measured assessment of natural wealth, it is necessary to use calculation methods based on the newly-implemented indices of natural capital’s economic assessment, along with the application of the available methods of the normative accounting using the data of the state assessment registers of natural resources. It is accented that the economic assessment of natural wealth in reliance upon substantial improvement of rating system is to provide possibilities to considerably improve the management system of the rational use and protection process of natural resources.